Assessment of occupational exposure from PET and PET/CT scanning in Saudi Arabia - Omer, Hiba; Salah, H.; Tamam, N.; Mahgoub, Omer; Sulieman, A.; Ahmed, Rufida; Abuzaid, M.; Saad, Ibrahim E.; Almogren, Kholoud S.; Bradley, D.A. * (Elsevier, 2023)
Nuclear medicine diagnostic procedures such as positron emission tomography (PET) scans and hybrid imaging using a combination of PET and computed tomography (CT), commonly referred to as PET-CT scanning. Hybrid imaging, which allows accurate visualization of internal anatomical structure and the consequent physiological processes simultaneously, is extensively used in oncology and other departments. Nevertheless, this exposes patients and medical personnel in such departments to significant doses of ionizing radiation, especially in hybrid imaging, where two sources of radiation (the radiopharmaceutical infusion and the CT scanner) are used. This necessitates strict compliance with international guidelines and regulations on radiation protection. Recent reports showed that occupational staff exposure might exceed the annual dose limits. This study evaluated occupational exposure associated with diagnostic hybrid PET-CT imaging and the consequent risks. Twenty medical personnel: 5 physicists, ten technologists, two medical doctors, and three nurses are included in this study. The assessment includes measuring occupational ambient doses using calibrated optical stimulating-luminescent dosimeters (OSL)(Al2O3:C). These badges were read using an automatic OSL reader. The results, displayed as (mean ± standard deviation): (range) of the effective dose (mSv) for the different personnel, can be summarized as follows(mean standard deviation and range). Physicists 0.72 ± 0.14 (0.49–0.83) mSv in 2019 and 0.67 ± 0.07 (0.59–0.78) in 2020; technologist 1.4 ± 0.96 (0–3.27) mSv in 2019 and 1.395 ± 1.27 (0.64–4.36) mSv; medical doctors 0.445 ± 0.42 (0.15–0.74) mSv in 2019 and 0.70 ± 0.04 (0.67–0.73) in 2020; and nurses 1.38 ± 0.25 (1.21–1.66) mSv in 2019 and 1.41 ± 0.17 (1.23–1.55) in 2020. The tube voltage of the scanner used in this study had a constant value of 120 kVp for all patients. Staff working in PET or PET-CT departments receive significant doses from the radiopharmaceuticals and the energetic gamma rays from the CT scanners. Hence, optimizing the CT acquisition parameter is necessary to optimize the occupational doses and restrict them to acceptable dose limits.